Modeling the Macroeconomic Impact of HIV/AIDS - Haacker, Markus (IMF Working Papers; Working Paper ;, 2002)
The paper addresses the impact of HIV/AIDS on per capita output and income, with particular emphasis on the role of labor mobility between the formal and informal sectors, and the impact of the epidemic on investment decisions. The study finds that HIV/AIDS affects both the supply of labor and the demand for labor in the formal sector. Only if there is a significant rise in the capital-labor ratio, will there be an increase in formal sector employment. However, this is associated with a decline in the rate of return to capital. To the extent that companies respond to this by reducing investment, conventional models underestimate the adverse impact on employment, per capita output, and income. The analysis of the impact of HIV/AIDS on output is complemented by an assessment of the impact on income.